Evaluating dealloying as a precursor to stress corrosion cracking: a micro-mechanical testing approach - Hooman Gholamzadeh; Kevin Daub; Mark R. Daymond; Suraj Y. Persaud (npj Materials Degradation)
Abstract Dealloying (selective dissolution) results in the formation of a (nano)porous film which has been proposed to act as a precursor to stress corrosion cracking (SCC) by a cleavage mechanism. The geometry of this film (e.g., ligament size and thickness) influences its ability to act as a precursor. This study investigates the micro-scale mechanical response of a dealloyed layer formed on Alloy 800 when exposed to boiling 50 wt% NaOH solution. Post-exposure in-SEM tensile and micro-cantilever bending tests were conducted on porous films of different geometries, formed after 2, 18 and 24 h of exposure. Results indicate that a porous dealloyed layer is more brittle compared to the base material and SCC can be induced, even with the corrosive environment removed. Increasing the time of exposure coarsened ligaments resulting in increased ductility of the porous film. In contrast, increasing the strain rate resulted in the porous film shifting towards brittle failure.